The effects of alcohol consumption in Thai society - pariyattikittithamrong, Phrakhru (Journal of International Buddhist Studies, 2016)
The purpose of this research; The effects of alcohol in Thai socciety, is to study alcohol-related behaviors in Thai citizens and how this action affects their lives on daily basis, to learn about the withdrawal process, to suggest preventions to decrease alcoholic habits and to support life improvement of the residents who reside in Saodiew Subdistrict, Nhonghong District Burirum Province. The founding results regarding habitant’s alcohol behavior suggest that 100% of those people were former drinkers, 60% initially started drinking when they were under the age of twenties. A motive of attempt the first alcohol consuming is socialization and a personal desire. Alcohol-related behaviors lead to health problems such as hypertension, alcoholism, and vehicle accidents, that could also result in the absence in workplace, family arguments, aggressive actions like; destroying objects in houses, fighting with neighbors. However, after discussing about the problems and solution, there were some helpful activities created in order to help drinkers’ reduce their alcoholic habits, for example, the village have granted several activities such as a campaign to prevent alcohol problems, a project called Sila 5 Village, severself organisation according to the village constitution or Thammanoon choomchon, a course for alcohol withdrawal guideline, Buddhism teachings, which can be applied in our everyday life, and activities to establish relationships in the village. The alcohol withdrawal practices and the principle improvement of people includes 1) Buddhist practices (The Five Percepts) 2) Health principles 3) Local supports from temples institution, the village, Local Administrative Organization and 4) activities for village relation. Those four items mentioned are positively influential in people’s alcohol habits; they help improve health conditions and quality of life.